Bioprinting of patient-derived in vitro intrahepatic cholangiocarcinoma tumor model: establishment, evaluation and anti-cancer drug testing. (28th July 2020) - Mao, Shuangshuang; He, Jianyu; Zhao, Yu; Liu, Tiankun; Xie, Feihu; Yang, Huayu; Mao, Yilei; Pang, Yuan; Sun, Wei
Abstract: Towards the development of in vivo -mimicking tumor model for extensive study of tumorigenesis and establishment of personalized therapy, patient-derived primary tumor cells were employed in this work for three-dimensional (3D) bioprinting. Intrahepatic cholangiocarcinoma cells isolated from patient were bioprinted using a composite hydrogel system of gelatin-alginate-Matrigel TM into pre-designed grid architecture. ICC cells were observed to process a colony forming ability with high survival rate and active proliferation. Expression levels of tumor markers, cancer stem cell markers, matrix metalloproteinase protein, index of tumor fibrosis, index of liver function, and epithelial-mesenchymal transition regulatory proteins confirmed the development of the invasive and metastatic phenotype of the intrahepatic cholangiocarcinoma cells in the 3D printed tumor microenvironment. Similar results were obtained in anti-cancer drug resistance of the intrahepatic cholangiocarcinoma cells in the 3D bioprinted construct that demonstrated stem-like properties, which suggested the promising potential of current 3D printed tumor model in the development of personalized therapy, especially for discovery of more conducive targeted drugs.